Public Transportation Line Passenger Prediction Using Mamdani Method of Fuzzy Logic to Foresee Holiday Passenger Surge - Elfira Makmur; Dessy Ana Laila Sari (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This study aims to predict the number of passengers on the Mall Pannakkukang-Galesong Harbor route on the